Fabrication of MoS2/TiO2 heterostructures with enhanced photocatalytic activity. Issue 22 (17th May 2019) - Lin, Yi; Ren, Pinyun; Wei, Chengyang
Abstract : Two-dimensional nanophotocatalysts MoS2 /TiO2 with a tunable decoration amount of MoS2 nanosheets were fabricated through a hydrothermal route. Abstract : Two-dimensional nanophotocatalysts MoS2 /TiO2 with a tunable decoration amount of MoS2 nanosheets were fabricated through a hydrothermal route. The microstructure and photocatalytic behaviors of the as-prepared samples were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, UV-vis diffuse reflectance spectroscopy, electrochemical workstation, dye degradation and water splitting experiments. The result shows that these composites exhibited enhanced photocatalytic activity for RhB degradation and hydrogen generation. Nearly 95% photocatalytic degradation of RhB was obtained for 2 h and 1.93 mmol g −1 h −1 hydrogen production rate was achieved over MoS2 /TiO2 at a MoS2 content of 10 wt%. And the corresponding photocurrent density of the composite photoelectrode was 5 times higher than that of pristine TiO2 architectures. It is believed that the boosted photocatalytic performance of the heterostructure could be ascribed to the synergetic effect between MoS2 and TiO2, which accelerated the separation and migration efficiency of charge carriers as well as enhancing the light-harvest efficiency.